2022
DOI: 10.3390/jcm11112971
|View full text |Cite
|
Sign up to set email alerts
|

Positive Orientation and Fatigue Experienced by Polish Nursing Students during the COVID-19 Pandemic: The Mediatory Role of Emotional Control

Abstract: This study aimed to investigate the mediatory role of emotional control with respect to the control of anger, depression, and anxiety in the relationship between positive orientation and tiredness/fatigue occurring in a group of Polish nursing students during the COVID-19 pandemic. The study included 894 nursing students from six universities in Poland. A diagnostic survey was applied as the research method, and the data were collected using the Fatigue Severity Scale (FSS), the Courtauld Emotional Control Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 82 publications
5
10
0
1
Order By: Relevance
“…In turn, in both studies by Malinowska-Lipień et al (2021a , b) , conducted among nurses during the second wave of the pandemic in Poland, the average level of emotional control was much higher and oscillated around 54. On the other hand, the average level of emotional control in a group of nursing students, in a study conducted at a similar time as research described in the present study, was about 51points in Poland, 51.40 in Spain and 52.69 in Slovakia ( Kupcewicz et al, 2022a , b ). The result obtained in this study (51.82) indicated an average level of emotional control and was comparable to the above-mentioned studies.…”
Section: Discussionsupporting
confidence: 76%
“…In turn, in both studies by Malinowska-Lipień et al (2021a , b) , conducted among nurses during the second wave of the pandemic in Poland, the average level of emotional control was much higher and oscillated around 54. On the other hand, the average level of emotional control in a group of nursing students, in a study conducted at a similar time as research described in the present study, was about 51points in Poland, 51.40 in Spain and 52.69 in Slovakia ( Kupcewicz et al, 2022a , b ). The result obtained in this study (51.82) indicated an average level of emotional control and was comparable to the above-mentioned studies.…”
Section: Discussionsupporting
confidence: 76%
“…Since then, several studies indicated that vaccination-induced antibodies could still neutralize the majority of the Omicron mutations, despite some cases showed low affinity and specificity. This is most likely due to the mutation at E484A, which leads to the reduced recognition and neutralization ( Kupcewicz et al., 2022 ). According to clinical data, unvaccinated or partly vaccinated cases have an higher risk of developing severity, which indicates that the vaccines are still effective to prevent severe disease ( Elbogen et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mean score for positive orientation as measured in this study was 26.25 points and was lower than in the normalisation sample (29.19 points) [ 45 ], as well as in an international study among students in Spain (M = 29.20) and Slovakia (M = 29.22) [ 18 ] and in a multi-centre study in Poland, also conducted among students of medical majors (26.87 points) [ 46 ]. The findings of this study show that more than half of the respondents had scores indicative of low levels of positive orientation.…”
Section: Discussionmentioning
confidence: 74%